What determines administrative capacity in developing countries? - Roberto Ricciuti; Antonio Savoia; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
While it is recognized that effective state institutions are pivotal for economic development, it is not well understood what their origins are and what explains their cross-country differences. We focus on budget institutions in developing economies, as efficient public finance planning in such countries is crucial for public goods and services provision. We argue that political institutions, seen as stronger system of checks and balances on the executive, are a key ingredient to build such capacity. Exploiting a recent database on public financial management performance in developing economies and an Instrumental Variable strategy, we generally find that stronger constraints on the executive have a positive effect on the ability of states to design, implement and monitor the budget. Our findings are robust to different specifications, controls, and estimation methods.
Keywords: H61; H83; P48; 330; state capacity; administrative capacity; public finance management; governance; economic development; budget institutions